Patient perspectives on depot buprenorphine treatment for opioid addiction - a qualitative interview study - Björn Johnson; Olivia Liahaugen Flensburg; Andrea Johansson Capusan (BMC, 2022)
Abstract Background Recently developed buprenorphine depot injections have the potential to reduce risk for diversion and misuse, and to increase adherence with fewer visits for supervised intake. However, it is unclear how patients perceive this new form of medication. The purpose of this study was to explore patients' experiences of depot injections and their reasons for continuing, discontinuing, or declining depot injection treatment. Methods We conducted semi-structured qualitative interviews with 32 people, 14 of whom had ongoing depot injection treatment, 11 who had discontinued depot-injections and switched to other medication and seven who had declined treatment with depot formulations. Interviews were transcribed, coded, and analysed using NVivo, based on this overall stratification into three participant groups. Results The main categories relate to the effects and side effects of the depot formulation, social and practical factors, psychological benefits and disadvantages, and interactions with treatment staff. Social and practical factors were of importance for choosing depot formulations, such as increased freedom and their making it easier to combine treatment with work and family life, as well as psychological advantages including "feeling normal". Initial withdrawal symptoms that resolved themselves after a number of injections were reported by most participants. Reliable information and patient-staff relationships characterized by trust helped patients to cope with these initial problems. Those who discontinued treatment often did so near the beginning of the treatment, reporting withdrawal symptoms and insufficient effects as the main reasons. Coercion and insufficient information contributed to a negative pharmaceutical atmosphere at one of the clinics, which may have adversely influenced perceptions of depot formulations and decreased willingness to accept and continue treatment. Conclusions Buprenorphine depot injections may have social, practical, and psychological benefits compared to other formulations. However, depot injections are not perceived as an attractive option by all patients. Trust, consistent and adequate information, and awareness of the implications of the pharmaceutical atmosphere should be considered when introducing new medications.